Mānuka oil based ECMT-154 versus vehicle control for the topical treatment of eczema: study protocol for a randomised controlled trial in community pharmacies in Aotearoa New Zealand - Gabrielle Shortt; Nicholas Shortt; Georgina Bird; Kyley Kerse; Nico Lieffering; Alexander Martin; Allie Eathorne; Bianca Black; Bob Kim; Marius Rademaker; Louise Reiche; Selwyn Te Paa; et al. (BMC, 2024)
Abstract Background Eczema is a chronic, relapsing skin condition commonly managed by emollients and topical corticosteroids. Prevalence of use and demand for effective botanical therapies for eczema is high worldwide, however, clinical evidence of benefit is limited for many currently available botanical treatment options. Robustly-designed and adequately powered randomised controlled trials (RCTs) are essential to determine evidence of clinical benefit. This protocol describes an RCT that aims to investigate whether a mānuka oil based emollient cream, containing 2% ECMT-154, is a safe and effective topical treatment for moderate to severe eczema. Methods This multicentre, single-blind, parallel-group, randomised controlled trial aims to recruit 118 participants from community pharmacies in Aotearoa New Zealand. Participants will be randomised 1:1 to receive topical cream with 2% ECMT-154 or vehicle control, and will apply assigned treatment twice daily to affected areas for six weeks. The primary outcome is improvement in subjective symptoms, assessed by change in POEM score. Secondary outcomes include change in objective symptoms assessed by SCORAD (part B), PO-SCORAD, DLQI, and treatment acceptability assessed by TSQM II and NRS. Discussion Recruitment through community pharmacies commenced in January 2022 and follow up will be completed by mid-2023. This study aims to collect acceptability and efficacy data of mānuka oil based ECMT-154 for the treatment of eczema. If efficacy is demonstrated, this topical may provide an option for a novel emollient treatment. The community-based design of the trial is anticipated to provide a generalisable result. Ethics and dissemination Ethics approval was obtained from Central Health and Disability Ethics Committee (reference: 2021 EXP 11490). Findings of the study will be disseminated to study participants, published in peer-reviewed journal and presented at scientific conferences. Trial registration Australian New Zealand Clinical Trials Registry (ANZCTR) ACTRN12621001096842. Registered on August 18, 2021 ( https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=382412&isReview=true ). Protocol version 2.1 (Dated 18/05/2022).